Combined effect of genetic background and gender in a mouse model of bleomycin-induced skin fibrosis - Ruzehaji, Nadira (Arthritis Res Ther, 2015)
INTRODUCTION: Systemic sclerosis (SSc) is a connective tissue disorder characterised by the development of skin fibrosis. Our current understanding of the disease pathogenesis is incomplete and the study of SSc is hindered, at least partially, by a lack of animal models that fully replicate the complex state of human disease. Murine model of bleomycin-induced dermal fibrosis encapsulates important events that take place early in the disease course. METHODS: To characterise the optimum in vivo parameters required for the successful induction of dermal fibrosis we subjected three commonly used mouse strains to repeated subcutaneous bleomycin injections. We aimed to identify the effects of genetic background and gender on the severity of skin fibrosis. We used male and female Balb/C, C57BL/6, and DBA/2 strains and assessed their susceptibility to bleomycin-induced fibrosis by measuring dermal thickness, hydroxyproline/collagen content and number of resident myofibroblasts, all of which are important indicators of the severity of skin fibrosis. All data are expressed as mean values ± SEM. The Mann–Whitney U test was used for statistical analysis with GraphPad Prism 6.04 software. RESULTS: Dermal fibrosis was most severe in Balb/C mice compared to C57BL/6 and DBA/2 suggesting that Balb/C mice are more susceptible to bleomycin-induced fibrosis. Analysis of the effect of gender on the severity of fibrosis showed that male Balb/C, C57BL/6, DBA/2 mice had a tendency to develop more pronounced fibrosis phenotype than female mice. Of potential importance, male Balb/C mice developed the most severe fibrosis phenotype compared to male C57BL/6 and male DBA/2 as indicated by significantly increased number of dermal myofibroblasts. CONCLUSION: Our study highlights the importance of genetic background and gender in the induction of murine dermal fibrosis. Robust and reproducible animal models of fibrosis are important research tools used in pharmacological studies which may lead to better understanding of the pathogenesis of fibrotic diseases and assist in identification of new drugs.